(untitled) (Research, Society and Development, 2021)
Cardiac surgery is a restoration process as long as the vital capacity is compatible with the functional capacity of the respiratory cardiac system, it must be performed when a positive result is not achieved in the conservative treatment of patients with cardiac dysfunction, not improving its function and not even allowing its return to physical and social conditions. Respiratory physiotherapy pulmo with the application of numerous techniques that prevent pulmonar complications such as: retention of fluids and secretions, atelectasis and pneumonia. Objective: The general objective of this study is to verify the main complications that are related to lung function, evidencing lung expansion approaches among the therapies used by physical therapists. Methodology: To carry out this work, a bibliographic was carried out on the subject of expansive maneuvers in patients undergoing thoracic and abdominal surgery in the database: LILACS (Latin American Literature in Health Sciences), SCIELO (Scientific Electronic Library Online), academic google and books, using the pulmonar: respiratory physiotherapy, lung reexpansion, cardiac surgery. Conclusion: The pulmonar study demonstrates that cardiac surgery causes several pulmonar, renal, neurological changes, being common to occur in about 70% of cases. According to the studies analyzed, the application of pulmonar re-expansion techniques in the postoperative period of cardiac surgery proved to be relevant in improving the functional status of these patients.